Total Phenols, Antioxidant Potential and Tyrosinase Inhibitory Activity of Walnut (Juglans regia L.) Leaf, Husk and Seed - Akin, M.; Arabaci, G.; Saki, N. (Asian Journal of Chemistry, 2013)
The present study reports the total phenolic contents, antioxidant potentials and tyrosinase inhibitory activity of the leaf, green husk and seed of walnut (Juglans regia L.) produced in Turkey. The total phenolic contents and antioxidant activity studies were carried out at two different extraction times (2 and 18 h) while the anti-tyrosinase activity was investigated at 2 h extraction time. For both extraction times, leaf extracts showed the highest amount of phenols [121.08 and 133.05 mg/g of gallic equivalent (GAE)] and DPPH (2,2-diphenyl-1-picrylhydrazyl) scavenging activity (86.66 and 93.33 %), respectively and the inhibitory efficiency of leaf extract (IC50 3.99 mg/mL) was determined to be much stronger than the seed and husk extracts. The inhibition type and Ki values were determined for the extracts. The results of this study suggested that walnut leaf, husk and seed can be used as an excellent, easily accessible source of natural antioxidant as well as the tyrosinase inhibitor.